TRADISI SUKU DAYAK KANAYATN DALAM PROSESI KELAHIRAN DAN KEMATIAN DI SUNGAI AMBAWANG KALIMANTAN BARAT - Yusawinur Barella; Aminuyati Aminuyati; Maya Saputri; Oktapiani Risti; Yuyun Wahyuni; Nazira Ayu; Siska Siska (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
This research was conducted in the village of Lingga, Sungai Ambawang District, Kubu Raya Regency. The research topic focuses on the birth and death of the Kanayatn Dayak tribe. This study aims to introduce the procession of birth and death of the Dayak Kanayatn tribe. The research methodology for preparing this article uses literature review and observation. Several findings are the result of this study. First, the Kanayatn Dayak tribe is one of the Dayak sub-tribes which has various kinds of uniqueness in its customs, such as birth and death processions. Second, the birth of the Dayak Kanayant tribe was carried out in four stages, namely summoning a shaman, preparing offerings, giving a name, and reciting a spell. Third, the death of the Dayak Kanayant tribe is carried out in five stages, namely, forgiveness, washing the corpse, and burial, three days and seven days.